Preliminary study on the effect of freshness of raw material on the quality of canned tuna. - De La Cruz, Maribel C. (College of Fisheries, University of the Philippines in the Visayas, 1985)
The effect of handling the raw materials used in processing canned tuna was studied by analyzing the finished products physically (sensory evaluation) and chemically. Tuna fish (Euthynnus affinis) held at ambient temperature (28-30℃) for 0, 3, 6, 9 and 12 hours after catch were heat processed for 60 minutes at 121.1℃ in 1F cans (307 x 201.25 inch). Assessment of quality was done by a taste panel and through chemical tests (k-value and histamine determinations). The mean sensory scores of canned tuna samples and the holiday time of raw material (at ambient temperature) gave a significant linear relationship at 1% level (r=0.98-0.99) results of sensory evaluation showed that delays up to 6 hours at ambient temperature before processing gave highly acceptable canned products, beyond this time, inferior quality described as bitter and fishy flavor and crumbling meat was obtained particularly after 12 hours. Statistical analysis (ANOVA and DMRT) of sensory scores revealed highly significant differences among the samples. The decline in sensory attributes (flavor, odor, texture) was accompanied by an increase in k-value and histamine level. However, values were found to be insignificant even after 12 hours daily from an initial value of 27%, k-value increased only to 49%, while histamine increased only 1.12 mg% from that initial value of 0.66 mg%. These final values were far less than the acceptable limits, that is, below 60% for K-value and below 10 mg% for histamine. Tuna canned after 13-day-storage in ice with delays-in-icing obtained K-values higher than 60%. Histamine, on the other hand, remained below the 10mg%-regulatory limit. All the canned samples made from these raw materials were rejected by the taste panel.